PREPARTUM URINE pH AS A PREDICTOR OF LEFT DISPLACEMENT OF ABOMASUM - Z. Mecitoglu; S. Senturk; C. Kara; G. Akgul; E. Uzabacı (Journal of Animal and Plant Sciences, 2016)
The aim of this study was to investigate the relationship between prepartum urine pH, blood ionized calcium, and blood pH levels and the incidence of left displacement of abomasum (LDA). Holstein dairy cows (n=115) in their second lactation were selected for the study. Urine and blood samples were collected seven days prior to the expected calving date, and urine pH, blood ionized calcium, and blood pH levels were measured. Of 115 cows, 13 (11%) had LDA at 15 (±7) days postpartum. Urine pH (LDA group: 6.11; healthy control group: 6.65) and blood pH (LDA group: 7.27; healthy control group: 7.37) levels were lower (P<0.05) in the LDA group than in the healthy control group. The sensitivity of urine pH, blood ionized calcium, and blood pH was 46, 62, and 84.6%, respectively, with corresponding specificities of 80.2, 61, and 44.1%. The results revealed that the measurement of urine pH levels in the last days of the dry period represents an inexpensive and fast method for predicting LDA. Future studies should incorporate dry matter intake calculations and larger sample sizes to evaluate the usefulness of urine pH in predicting LDA in practice.
Keywords: Urine pH; LDA; DCAD; overacidification